2021
DOI: 10.15586/ijfs.v33i2.1918
|View full text |Cite
|
Sign up to set email alerts
|

The influence of starter cultures on the lactic acid bacteria microbiota of Petrovac sausage

Abstract: Petrovac sausage (Petrovská klobása) is a high-quality fermented dry sausage produced traditionally in the municipality of Ba?ki Petrovac (Vojvodina, Serbia). The product is characterised by specific and recognised texture, aroma and colour, produced without additives or preservatives. Lactic acid bacteria (LAB) microbiota plays an important role in production of the sausage. The aim of the paper is to monitor the changes in LAB during the production of Petrovac sausage. Samples of sausages were prepared witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Class III contains lysins (class IIIa) and nonlytic BACs (class IIIb). Class IV contains circulating inhibitory peptides such as enterocin AS-48 (Favaro et al, 2015;Milicevic et al, 2021).…”
Section: Glucose Oxidasementioning
confidence: 99%
See 2 more Smart Citations
“…Class III contains lysins (class IIIa) and nonlytic BACs (class IIIb). Class IV contains circulating inhibitory peptides such as enterocin AS-48 (Favaro et al, 2015;Milicevic et al, 2021).…”
Section: Glucose Oxidasementioning
confidence: 99%
“…Also, BACs and other methods as a hurdle can be helpful (Favaro et al, 2015). BACs are used in food products because they are harmless, do not change foods' nutritional characteristics, are efficient in low concentration, and active in refrigerator storage, and, therefore, an ideal bio-preservation (Mahmud and Khan, 2018;Milicevic et al, 2021). BACs isolated from G + bacteria are classified into the following groups: Class I, Class II, Class III, and Class IV.…”
Section: Bacteriocinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, biological decontamination methods using bacteria, fungi, yeasts, enzymes and plants have generated interest among researchers. Probiotic bacteria can also be applied to this object (Mahmmodi et al ., 2021; Milićević et al ., 2021; Mirmahdi et al ., 2021; Mohajeri et al ., 2021). Studies showed that aflatoxins could bind to bacterial cell walls, including peptidoglycans and polysaccharides, reducing their bioavailability (Pizzolitto et al ., 2011; Pires et al ., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Today, humans pay considerable attention to food safety and contaminants (Milicevic et al, 2021;Rapa et al, 2021;Xinyu et al, 2020). Mycotoxins produced by fungi are among the most important food contaminants and have a negative impact on public health, food safety, and the national economy of many countries, especially developing countries (Batrinou et al, 2020;Grumi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%